Go2Work: A Staff Attendance System using QR Code with CAOQTP Algorithm for Pejabat Pendidikan Hulu Langat - Mohd Khairi, Muhammad Nafies Riza; Abd Warif, Nor Bakiah (Applied Information Technology And Computer Science, 2025)
Nowadays, attendance systems play a pivotal role in diverse sectors, ranging from educational institutions to corporate settings. The evolution of these systems has witnessed a shift from traditional manual methods to more advanced and technology-driven solutions. The creation of GO2WORK, a sophisticated staff attendance system that makes use of QR codes and the CAOQTP algorithm, is the project’s primary goal. To solve the problem that OTP randomly generated characters that can be predicted by bots, CAOQTP adds an extra layer of security by adding CAPTCHA images that user must rearrange according to the received OTP. Additionally, to solve the problem of attendance fraud, the QR code can only be generated at designated kiosk. Moreover, user must scan the QR code within the range of the kiosk. Hence, preventing user to take attendance outside the range of the workplace area. Furthermore, the project moves through steps including requirement gathering, quick design, building a prototype, user evaluation, refining the prototype, implementation, and maintenance using the prototyping model. GO2WORK is designed specifically to be used in educational institutions and organizational contexts, with the goal of transforming attendance tracking. A user-friendly, safe, and effective system with real-time monitoring capabilities is what’s anticipated, offering improved security, accuracy, and administrative effectiveness. A revolutionary step towards modernizing attendance management procedures is GO2WORK.